Perjuangan Perempuan pada Masa Pergolakan Politik Indonesia Tahun 1965 dalam Novel Gadis Jakarta Karya Najib Kaelani dan Novel Amba Karya Laksmi Pamuntjak - Dinar Eka Wijayanti (Aphorisme: Journal of Arabic Language, Literature, and Education, 2020)
This research focused on comparing the struggle of a woman during the Indonesian political upheaval 1965 in the novel of Gadis Jakarta by Najib Kaelani and the novel of Amba by Laksmi Pamuntjak. Using a comparative analysis descriptive research method, the research show results that there are similarities in the two novels. First, both novels' main character is an educated woman who has education up to college and both colleges at the Faculty of Literature. Second, the time of events in the two novels is the same (during the Indonesian political upheaval 1965), in which the G30S/PKI rebellion took place. Third, the place settings in both novels are also similar (in Jakarta's capital city). Fourth, loved ones who want to be saved by the main characters in both novels are people who are being loved by the main character. Fifth, in both novels, there is a similarity in women's struggle in saving their love who were kidnapped during the PKI rebellion. In addition to the similarities above, there are also differences in the two novels. First, in Gadis Jakarta, from the beginning to the end of the story, the writer told only about the period of Indonesian political upheaval 1965. In contrast, Amba did not. Secondly, the main character in Gadis Jakarta died after being shot, while the main character in Amba lives up to the end of the story. Third, the fate of the characters saved or sought after by the main characters in the two novels is also different.